Influence of different urine preservation methods and addition of preservatives on quantitative detection of 24-h urinary protein - Bao, Xinxin; Sun, Xiaoye; Geng, Haiying; Yuan, Xiaohua (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to elucidate the effect of adding xylene as a preservative on 24-h urine protein quantification under different storage temperatures.MethodsFrom January 2020 to August 2020, our hospital selected a total of 80 samples with positive results of urine protein. Under different storage temperature conditions, urine samples containing or not containing xylene were collected simultaneously. Then, one-way analysis of variance was used to study the effects of preservatives and temperature on the 24-h urine protein quantification test. Receiver operating characteristic (ROC) analysis was used to examine the effect of adding preservatives on the accuracy of the 24-h urinary protein concentration determination.ResultsBased on the results of the control group, there was no statistically significant difference in the 24-h urine protein concentration between the preservative group and the group without preservatives at 37, 24–26 or 4 °C (F = 0.006, P = 0.993; F = 0.013, P = 0.987; F = 0.022, P = 0.977). The results of the ROC analysis indicated excellent diagnostic accuracy for proteinuria detection across all storage conditions (AUC: 0.992–0.994). The accuracy of urine samples stored without preservatives was comparable to, and in some cases (e.g., at 4 °C) exhibited perfect specificity (100%) alongside high sensitivity (97.4%), matching the direct detection in the control group.ConclusionStoring 24-h urine protein specimens at room temperature without using preservatives is a safe, simple, and feasible method. This method is suitable for wide application in clinical practice.